Diagnostic Criteria of Acute Transverse Myelitis - J Gordon Millichap (Pediatric Neurology Briefs)
Inclusion and exclusion criteria for the diagnosis of acute transverse myelitis (ATM), as a basis for multicenter clinical trials, are proposed by a Transverse Myelitis Consortium Working Group.